Queer Methods and Methodologies - Browne, Kath; Nash, Catherine J. (Routledge, 2010)
This interdisciplinary volume provides the first systematic consideration of the implications of a queer perspective in the pursuit of social scientific research. It will appeal to anyone pursing research at the intersections between social scientific research and queer perspectives, as well as those engaging with methodological considerations in social science research more broadly
Description based on print version record.
KU Select 2017: Backlist Collection
Keywords: Social Science / Anthropology; Social sciences; Electronic books